Gaya Bicara Manja sebagai Representasi Kognisi Bahasa Anak: Studi Kasus Psikolinguistik - Alda Amanatun Khoiriyah; Tatang Hariri (Jurnal Bahasa dan Sastra, 2026)
The child’s playful speech style is not merely an individual form of expression, but also a communication strategy employed to build closeness and influence the interlocutor’s response. This study aims to identify the speech strategies used in playful speaking as well as the socio-emotional factors underlying the emergence of this style in the subject AFR, an eight-year-old child. Using a qualitative descriptive approach, the study found that AFR’s playful speech style is characterized by word reduplication, phoneme omission and substitution, rising and elongated intonation, and the use of special forms of address. Data were collected in both home and school settings trough the Simak Bebas Libat Cakap (SBLC) method, followed by note-taking, providing direct insight into the contexts of use. Furthermore, AFR’s speech strategies include bald on record, positive politeness, negative politeness, and off-record strategies. The style appears predominantly in interactions with close family members and rarely in school, shaped by socio-emotional closeness and executive functions such as inhibitory control, cognitive flexibility, and emotional regulation. These findings affirm that coquettish speech is not a spontaneous childish act but a manifestation of psycholinguistic processes rooted in cognitive mechanisms, reflecting the child’s understanding of interpersonal relations. This study contributes to child psycholinguistics by offering new perspectives on how children’s language us reflects not only structural development but also the social and emotional dynamics shaping everyday interaction.